The Awareness of Pharmacovigilance among Medical Doctors in a Tertiary Care Teaching Hospital - Sapna Patil; P. A. Patil; S. Javali; Ameeta Patil; Heethal Jaiprakash (Pharmaceutical Research: Recent Advances and Trends Vol. 6, 2024)
Aims: The present study aimed to assess the knowledge, attitude and practice of ADR reporting among interns and clinical post-graduates in a tertiary care teaching hospital. Background: Adverse Drug Reactions (ADRs) are an important cause of morbidity and mortality worldwide. Spontaneous reporting of ADRs has played a major role in the detection of suspected, serious, and unusual ADRs previously undetected during the clinical trial phases. ADRs are a threat to the patient’s safety as well as the quality of life and they increase the health care cost considerably. Spontaneous reporting of ADRs has played a major role in the detection of suspected, serious, and unusual ADRs previously undetected during the clinical trial phases. Proper monitoring and reporting of ADRs for the prevention and management of ADRs is the need of the hour. Methodology: This was an observational, questionnaire-based study. A pre-validated questionnaire (from previous studies) containing both open and close-ended items was used as the evaluation tool. One hundred and fifty-two interns and clinical post-graduates were included in the study. Participation in the study was voluntary and without any obligation. The study was rolled out after receiving approval from the Institutional Ethics Committee. The previously validated questionnaire consisting of a total of 24 items was distributed to the health care professionals. The data was analysed using the Chi-square test, one-way ANOVA and Karl Pearson’s co-efficient of correlation tests with the help of SPPS software 20.0. Results: Out of 152 participants, 48(31.6%) were year 1, 44(28.95%) were year 2 clinical post-graduate students; as compared to 60(39.47%) interns. Thirty-two (21.1%) participants out of which 20 interns, 7(14.6%) year 1 and 5(11.4%) year 2 clinical postgraduates, had knowledge of the local peripheral monitoring centre. The difference was found to be statistically significant (p<0.05). 88.2% of the total participants had never reported an ADR to the pharmacovigilance centre. There was no significant difference among the three groups of participants, in terms of mean scores of knowledge, attitude and practice (p>0.05), but there was a significant (p<0.05) and positive correlation between knowledge and practice (r=0.2110) and attitude and practice (r=0.2415). Pharmacovigilance programmes have played a major role in the detection of ADRs and the banning of several drugs from the market. However, underreporting of ADRs is one of the major problems associated with Pharmacovigilance programmes. Conclusion: The training of pharmacovigilance activities should start early in the professional training of doctors and needs to be reinforced during the postgraduate course. There is a great need to create awareness regarding Pharmacovigilance and to promote the reporting of ADR amongst healthcare professionals. The health care professionals should realize that ADR reporting is an integral part of their clinical activities and this is very necessary for better patient care.